Positive symptoms associate with cortical thinning in the superior temporal gyrus via the ENIGMA Schizophrenia consortium. (29th March 2017) - Walton, E.; Hibar, D. P.; van Erp, T. G. M.; Potkin, S. G.; Roiz‐Santiañez, R.; Crespo‐Facorro, B.; Suarez‐Pinilla, P.; Van Haren, N. E. M.; de Zwarte, S. M. C.; Kahn, R. S.; Cahn, W.; Doan, N. T.; et al.
Abstract : Objective: Based on the role of the superior temporal gyrus (STG) in auditory processing, language comprehension and self‐monitoring, this study aimed to investigate the relationship between STG cortical thickness and positive symptom severity in schizophrenia. Method: This prospective meta‐analysis includes data from 1987 individuals with schizophrenia collected at seventeen centres around the world that contribute to the ENIGMA Schizophrenia Working Group. STG thickness measures were extracted from T1‐weighted brain scans using FreeSurfer. The study performed a meta‐analysis of effect sizes across sites generated by a model predicting left or right STG thickness with a positive symptom severity score (harmonized SAPS or PANSS‐positive scores), while controlling for age, sex and site. Secondary models investigated relationships between antipsychotic medication, duration of illness, overall illness severity, handedness and STG thickness. Results: Positive symptom severity was negatively related to STG thickness in both hemispheres (left: βstd = −0.052; P = 0.021; right: βstd = −0.073; P = 0.001) when statistically controlling for age, sex and site. This effect remained stable in models including duration of illness, antipsychotic medication or handedness. Conclusion: Our findings further underline the important role of the STG in hallmark symptoms in schizophrenia. These findings can assist in advancing insight into symptom‐relevant pathophysiological mechanisms in schizophrenia.